The Treg/Th17 Axis: A Dynamic Balance Regulated by the Gut Microbiome - Omenetti, Sara; Pizarro, Theresa T. (Frontiers in Immunology, 2015)
T-helper 17 (Th17) and T-regulatory (Treg) cells are frequently found at barrier surfaces, particularly within the intestinal mucosa, where they function to protect the host from pathogenic microorganisms and to restrain excessive effector T-cell responses, respectively. Despite their differing functional properties, Th17 cells and Tregs share similar developmental requirements. In fact, the fate of antigen-naïve T-cells to either Th17 or Treg lineages is finely regulated by key mediators, including TGFβ, IL-6 and all-trans retinoic acid (RA). Importantly, the intestinal microbiome also provides immunostimulatory signals, which can activate innate, and downstream adaptive, immune responses. Specific components of the gut microbiome have been implicated in the production of proinflammatory cytokines by innate immune cells, such as IL-6, IL-23, IL-1β, and the subsequent generation and expansion of Th17 cells. Similarly, commensal bacteria and their metabolites can also promote the generation of intestinal Tregs that can actively induce mucosal tolerance. As such, dysbiosis of the gut microbiome may not solely represent a consequence of gut inflammation, but rather shape the Treg/Th17 commitment and influence susceptibility to inflammatory bowel disease (IBD). In this review, we discuss Treg and Th17 cell plasticity, its dynamic regulation by the microbiome, and highlight its impact on intestinal homeostasis and disease.